Heterogeneity in the trajectories of US Latine mothers' dual-language input from infancy to preschool. Issue 3 (June 2020) - Luo, Rufan; Escobar, Kelly; Tamis-LeMonda, Catherine S.
We longitudinally examined the trajectories of Latine mothers' ( N = 116) language input to their children during book-sharing interactions at four points in development, when children were between ages 2 and 5 years. Mother–child dyads were video-recorded sharing a wordless picture book, and transcriptions of mothers' and children's language yielded word types in Spanish and English at each assessment wave. Three distinct trajectories of change in mothers' dual-language use were identified. Some mothers shifted from Spanish-dominant input to more balanced input between English and Spanish; other mothers provided English-dominant input and used more English and less Spanish over time; and the remaining mothers were stable in their Spanish-dominant input across child ages. Mothers' immigration background, educational level, and children's preschool language experiences each uniquely predicted trajectories of maternal language input. In general, children showed similar trajectories as their mothers, although mismatch occurred for some dyads at the later ages. The dual-language environments of Latine children are dynamic and shaped by individual and contextual factors.